2021
DOI: 10.48550/arxiv.2103.16462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonlinear rheology of cellular networks

Abstract: Morphogenesis depends crucially on the complex rheological properties of cell tissues and on their ability to maintain mechanical integrity while rearranging at long times. In this paper, we study the rheology of polygonal cellular networks described by a vertex model in the presence of fluctuations. We use a triangulation method to decompose shear into cell shape changes and cell rearrangements. Considering the steady-state stress under constant shear, we observe nonlinear shear-thinning behavior at all magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Interestingly, in ordered ground states of the model, there is a distinction between the onset of rigidity determined by the shear modulus (which occurs at the shape index of a regular hexagon, p 0 ∼ 3.72), and when energy barriers disappear (at ). This suggests that there must be non-analytic cusps in the potential energy landscape Sussman and Merkel (2018 ); Popović et al (2021 ) and that there may be significant differences between the linear (zero strain rate, infinitesimal strain) and nonlinear (finite strain rate, finite strain) rheology of vertex models, which have recently been studied in 2D Duclut et al (2021 ); Basan et al (2011 ); Popović et al (2021 ) and 3D Sanematsu et al (2021 ).…”
Section: Models and Methodsmentioning
confidence: 99%
“…Interestingly, in ordered ground states of the model, there is a distinction between the onset of rigidity determined by the shear modulus (which occurs at the shape index of a regular hexagon, p 0 ∼ 3.72), and when energy barriers disappear (at ). This suggests that there must be non-analytic cusps in the potential energy landscape Sussman and Merkel (2018 ); Popović et al (2021 ) and that there may be significant differences between the linear (zero strain rate, infinitesimal strain) and nonlinear (finite strain rate, finite strain) rheology of vertex models, which have recently been studied in 2D Duclut et al (2021 ); Basan et al (2011 ); Popović et al (2021 ) and 3D Sanematsu et al (2021 ).…”
Section: Models and Methodsmentioning
confidence: 99%
“…These couplings play an essential role in the transmission of spatial information in large cell monolayers, which are often mediated by travelling waves, pulses, and a tug of war between cell-cell and cell-substrate forces [210,211]. While some recent progress has been made on incorporating these couplings in continuum models [212], informed by studies of mesoscopic models and by experiments, formulating an adaptive rheological model of tissue remains an open challenge. This is further complicated by the fact that living tissue is also capable of adapting its mechanical state in response to changes in environment, through feedback loops in a way that has so far largely eluded predictive theoretical descriptions.…”
Section: From Living Cells To Biological Tissuementioning
confidence: 99%
“…A growing number of theoretical studies has begun to address this gap. Various groups have used vertex-based models [54,55] to simulate the linear [56,57] and nonlinear [58] rheology of a tissue under steady shear flow. The effects of active tension fluctuations [58,59] and cell division [60] have been explored.…”
mentioning
confidence: 99%
“…Various groups have used vertex-based models [54,55] to simulate the linear [56,57] and nonlinear [58] rheology of a tissue under steady shear flow. The effects of active tension fluctuations [58,59] and cell division [60] have been explored. An earlier study [61] has also showed that the vertex model can reproduce a nonlinear mechanical response qualitatively similar to that observed experimentally [37].…”
mentioning
confidence: 99%